The suppression of superconductivity in MgCNi3 by Ni-site doping - Hayward, M; Haas, M; Ramirez, A; He, T; Regan, K; Rogado, N; Inumaru, K (2001)
The effects of partial substitution of Cu and Co for Ni in the intermetallic perovskite superconductor MgCNi3 are reported. Calculation of the expected electronic density of states suggests that electron (Cu) and hole (Co) doping should have different effects. For MgCNi3-xCux, solubility of Cu is limited to approximately 3% (x = 0.1). and Tc decreases systematically from 7 to 6 K. For MgCNi3-xCox, solubility of Co is much more extensive, but bulk superconductivity disappears for Co doping of 1% (x = 0.03). No signature of long range magnetic ordering is observed in the magnetic susceptibility of the Co doped material. © 2001 Elsevier Science Ltd. All rights reserved.